2008
DOI: 10.1186/1477-7819-6-51
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-assisted breast biopsy: A comparison of 11-gauge and 8-gauge needles in benign breast disease

Abstract: Background: Minimal invasive breast biopsy is standard care for the diagnosis of suspicious breast lesions. There are different vacuum biopsy (VB) systems in use. The aim of the study was to determine the differences between the 8-gauge and the 11-gauge needle with respect to a) diagnostic reliability, b) complication rate and c) subjective perception of pain when used for vacuum-assisted breast biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 16 publications
0
24
1
3
Order By: Relevance
“…As a result of the potential for complete excision, biopsy and a treatment for benign breast lesions were facilitated. The clinical experience gained in the present study indicated that the 8-gauge probe was suitable for the firm breast tissue due to its sharp scalpel point, and that it was appropriate for the complete removal of benign lesions under ultrasound guidance (31). Taking into consideration the capacity of the probe to obtain the samples and to lead to successful therapeutic outcomes, the use of the 8-gauge probe was maintained throughout the study.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…As a result of the potential for complete excision, biopsy and a treatment for benign breast lesions were facilitated. The clinical experience gained in the present study indicated that the 8-gauge probe was suitable for the firm breast tissue due to its sharp scalpel point, and that it was appropriate for the complete removal of benign lesions under ultrasound guidance (31). Taking into consideration the capacity of the probe to obtain the samples and to lead to successful therapeutic outcomes, the use of the 8-gauge probe was maintained throughout the study.…”
Section: Discussionmentioning
confidence: 75%
“…Increasing numbers of surgeons have attempted similar therapeutic procedures (21,27,28,3032). The application of an 8-gauge probe led to the possibility of larger-volume sampling and excision (31). As a result of the potential for complete excision, biopsy and a treatment for benign breast lesions were facilitated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider the Mammotome to be superior in terms of its accuracy in obtaining samples for the diagnosis of impalpable breast lesions. The smaller the tumor, the more easily it is removed 32 . Furthermore, It should be considered as a viable alternative to much more radical open surgical approaches when faced with the daunting task of removing multiple bilateral presumed benign lesions such as multiple fibroadenomas.…”
Section: Discussionmentioning
confidence: 99%
“…Since VAB gives the opportunity to remove relatively large tissue amounts, it can be used to excise small lesions as an alternative to open surgery for women with a known benign mass, who desire excision but prefer to avoid surgery or who are not suitable for surgery. VAB is well tolerated [32]. Thurley et al [33] performed ultrasound-guided VAB in 134 patients with benign lesions.…”
Section: Disclosure Statementmentioning
confidence: 99%